Patient Sleep- wake rhythms in hospital - Tootoonchi M (Iran University of Medical Sciences, 1991)
for most people iterance to hospital is a disturbing experience and expects that nurses be sensitive to patient's physical, emotional and social need at admission. Whereas interrupt of sleep due to physical, psychological and social status damage, knowing about effective mechanisms in retention and disturbance of sleep - wake cycles help nurses to make natural criteria for their patient's sleep. This article is review literature about sleep- wake cycles, sleeps function, source and factors affecting on normal sleep- wake cycles improvement or factors that due to disturbance in normal cycle in patient's hospitalization period